Delinquency in society - Regoli, Robert M. (McGraw-Hill, 2006)
In this conversational, jargon-free text with its clear and thorough presentation of theories of delinquency, Regoli and Hewitt make delinquency interesting to read about. It is no encyclopedic compendium, but a critical look at a very serious problem. .